Implementation of Deep Learning to Enhance Student Participation in Grade VIII Volleyball Learning - Dia Tri Pambayun; Anirotul Qoriah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study was motivated by the low level of student participation in volleyball learning, which was related to conventional teaching methods that did not fully encourage active student engagement. Therefore, instructional innovation is needed, one of which is the deep learning approach. This study aimed to describe the implementation of deep learning in improving student participation in volleyball learning. A quantitative approach with a descriptive survey method was used. The sample consisted of 64 Grade VIII students se-lected through purposive sampling. Data were collected through observation, question-naires, and documentation. The questionnaire was developed based on indicators of stu-dent participation and the principles of deep learning, namely mindful learning, meaning-ful learning, and joyful learning. The data were analyzed using descriptive statistics, includ-ing scores, means, standard deviations, frequencies, and percentages. The results showed that 52% of students were in the high category, 6% in the very high category, and 42% in the moderate category, with no students in the low category. These findings indicate that deep learning can create an active, meaningful, and enjoyable learning environment and can be used as an effective strategy to increase student participation in volleyball learning.